Edodin: A New Type of Toxin from Shiitake Mushroom (Lentinula edodes) That Inactivates Mammalian Ribosomes - Citores, Lucía (2024)
Ribosome-inactivating proteins (RIPs) are a group of proteins with rRNA N-glycosylase activity that irreversibly inhibit protein synthesis and consequently cause cell death. Recently, an RIP called ledodin has been found in shiitake; it is cytotoxic, strongly inhibits protein synthesis, and shows rRNA N-glycosylase activity. In this work, we isolated and characterized a 50 kDa cytotoxic protein from shiitake that we named edodin. Edodin inhibits protein synthesis in a mammalian cell-free system, but not in insect-, yeast-, and bacteria-derived systems. It exhibits rRNA N-glycosylase and DNA-nicking activities, which relate it to plant RIPs. It was also shown to be toxic to HeLa and COLO 320 cells. Its structure is not related to other RIPs found in plants, bacteria, or fungi, but, instead, it presents the characteristic structure of the fold type I of pyridoxal phosphate-dependent enzymes. Homologous sequences have been found in other fungi of the class Agaricomycetes; thus, edodin could be a new type of toxin present in many fungi, some of them edible, which makes them of great interest in health, both for their involvement in food safety and for their potential biomedical and biotechnological applications.